Heritability (h2) estimation of certain traits serving as measures of value in purebred Hungarian pig populations - Csató, László; Farkas, János; Groeneveld, Eildert; Radnóczi, László (Acta Agraria Kaposváriensis, 1998)
The authors performed variance component estimation on Hungarian pig breeds by means of the VCE 3.2 programme developed by Groeneveld (1993). Determination of If value was performed for four pure-bred types and two basic hybrid lines by the application of individual models. Two covariant variables, 5 fixed effects, one random(i.e., litter) and the characteristic effect were included in the models. The databases of the Hungarian operational individual performance examination (USTV) and the central station examination (HVT) were used simultaneously by the programme in the estimation process, h values for two traits were estimated from the USTV. Values between 0.14 and 0.33 were obtained for the trait relating to growth intensity, with a low degree of estimation error (between 2 and 8%). In the case of mean back fat thickness, which serves as an expression of slaughter value, the h2 values estimated fell into the range 0.13 to 0.33, with a standard error of 2 to 13%. The low h2 values obtained can be attributed to the so-termed confounding phenomenon, which occurs, through the mingling of the operational and the genetic effect, at genetically closed breeding sites. In the HVT h2 values for four traits were estimated. The heritability estimates obtained were the following: for the number of days of the fattening period, 0.24–0.46; for the quantity of diet consumed during the trial, 0.25–0.55; for the quantity of the valuable meat parts, 0.39–0.67; and for the meat quality points total, 0.04–0.21. Error in the heritability estimation varied between 3.0 and 24.8% for the first three traits, and between 14.1 and 61.6% for the fourth. Further estimations, founded on a larger database, are planned by the authors in an endeavour to provide an explanation for the differences in h2 value observed between breeds and genotypes.